2000
DOI: 10.1016/s0039-6028(00)00826-8
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate-induced substrate relaxation and the adsorbate–adsorbate interaction

Abstract: We formulate the theory of the perturbation caused by an adsorbate upon the substrate lattice in terms of a local modification of the interatomic potential energy around the adsorption site, which leads to the relaxation of substrate atoms. We apply the approach to CO chemisorption on closepacked metal surfaces, and show that the adsorbate-adsorbate interaction and a variety of other properties can be well described by a simple model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Although not as pronounced as Pt͕111͖, we have found that the Pt͕100͖ surface suffers from similar problems in the sense that binding at the atop site is underestimated, Table I. Some limited empirical descriptions of the CO/Pt interaction exist, 23,27 but to our knowledge, no realistic CO/Pt potential has been constructed yet.…”
Section: A the Coõpt Systemmentioning
confidence: 83%
See 1 more Smart Citation
“…Although not as pronounced as Pt͕111͖, we have found that the Pt͕100͖ surface suffers from similar problems in the sense that binding at the atop site is underestimated, Table I. Some limited empirical descriptions of the CO/Pt interaction exist, 23,27 but to our knowledge, no realistic CO/Pt potential has been constructed yet.…”
Section: A the Coõpt Systemmentioning
confidence: 83%
“…2 and agree reasonably well with the empirical relation for CO on Pt͕111͖ derived by Persson et al 28 Part of the discrepancy between the DFT calculations and the empirical data might be assigned to inhibited relaxations of the Pt surface. 27 This effect arises because an adsorbed CO molecule induces localized relaxations of the substrate lattice around the adsorption site and when another CO molecule is close enough, the perturbation caused by one CO molecule influences the other, and the total adsorption energy is not exactly the sum of the adsorption energies of the isolated adsorbates, i.e., an effective interaction energy appears. This indirect repulsion is not present in the DFT calculations, since the Pt substrate is kept fixed, see Sec.…”
Section: Co-co Parametersmentioning
confidence: 99%
“…These separations are almost twice as long as the typical chemical bond, including the hydrogen bond [24], and small changes in the separations when going from A(B)-to C-oriented domains will hardly change the strength of intermolecular interactions (mostly electrostatic in nature). We can also disregard the elastic substrate-mediated interactions between the neighbour molecules due to adsorption-induced shifting of lattice atoms, because these effects are characteristic of strongly binding adsorbates [25] while the binding energy of the CH 3 SH molecule on Au(1 1 1) is only $10 kcal/mol. The expected similar energetics among the three domains is also consistent with the fact that all three types of domains are initially observed in the real-time STM movies of the CH 3 SH monolayer formation taken at $50 K (Fig.…”
Section: Structural Differences Between Saturated Molecular Domainsmentioning
confidence: 99%
“…Our results show that a multitude of local minimum structures exists on supported Pt 13 clusters within a narrow energy window. Adsorbate-induced relaxation to the atoms making up the binding site can lead to a difference between the preadsorption cluster geometry and the postdesorption cluster geometry. Furthermore, the postdesorption cluster geometry can also vary depending on the adsorbate and adsorption site.…”
Section: Resultsmentioning
confidence: 99%